Reorientasi Kebijakan Non-Blok Swedia ke NATO: Analisis Strategi Balancing Threat Terhadap Ancaman Eksistensial Rusia - Semeion El Sozo; Deasy Silvya Sari (Jurnal Transformasi Global, 2026)
This study examines Sweden’s historic shift from military non-alignment to joining NATO as its 32nd member. Based on primary data from an interview with the Swedish Ambassador to Indonesia, H.E. Daniel Blockert, the research identifies Russia's full-scale invasion of Ukraine in February 2022 as the primary catalyst for this paradigm shift. The findings suggest that Sweden’s motivations were driven by an existential security threat and the strategic necessity of synchronizing defense policies with neighboring Finland. The integration offers fundamental advantages, including collective defense guarantees under Article 5, enhanced control over the Baltic Sea region which is now effectively a "NATO lake" and advanced military interoperability. However, the accession introduces significant challenges, such as the erosion of a 200-year-old identity of neutrality, fiscal burdens of meeting the 2% GDP defense spending requirement, and the diplomatic complexity of navigating NATO’s nuclear umbrella while maintaining anti-nuclear values. This study concludes that while NATO membership provides a robust security deterrent, Sweden must now navigate a complex landscape of administrative restructuring and evolving international perceptions in the Global South.